Impacto de los Influencers en las Estrategias Promocionales del Sector Gastronómico de la ciudad de Medellín - Sandra Milena AMAYA HENAO,Germán Augusto SILVA CORTÉS,Yanyn Aurora RINCÓN QUINTERO, (Fonseca, Journal of Communication, 2023)
Gastronomic influencers have become figures that highly influence the recognition and promotion of business in this sector and, in turn, allow the community to know the gastronomic diversity that can be found in the city of Medellin. This article aims to know the impact of influencers on the promotional strategies of the gastronomic sector of the city of Medellin, via descriptive research, based on a non-experimental, descriptive and field-based transectional design; us-ing as techniques for data collection the interview and the survey through a multivariate, or multiple options question-naire.